Quality control problems encountered by foreign buyers - Cabili, Lenora Luisa Alano; Ynchausti, Natividad S. (1992.)
This survey aims to know specifically what quality control problems in construction, appearance, fabric and packaging are frequently encountered by foreign buyers in their orders made within the last 12 months; and the average period of delay in those shipments. To analyze and find solutions to the top ten (10) quality control problems. A questionnaire was created based on some quality control manuals and final inspection reports. The questionnaire consisted of problems in construction, appearance, fabric and packaging stated in the negative. Questionnaires were mailed to the foreign buyers with a self-stamped envelope which was to be used to return the questionnaires. Twenty (20) questionnaires were returned but only nineteen (19) were valid. The Descriptive method was used to interpret the data. Ranking was used to determine the top ten (10) problems which are the following: 1. skip, cut or broken stitches (construction). 2. stains and soils (appearance) 3. threads threads not trimmed (appearance) 4. excessive tight/loose tension (construction) 5. unslightly overlap stitches (construction)6. seams twisted, puckered, pleated (construction) 7. distorted, misaligned seam (construction) 8. button missing, misplaced, insecure (construction) 9. uncut buttonhole, noticeable bulge, poorly cut (construction) 10. generally untrimmed garment (appearance). Generally, the problems encountered were in the construction and appearance of the garment. Garment manufacturing companies should constantly upgrade their quality control system and carefully handle the storage of every garment they finish. The average period of delay in shipments was 8 to 14 days. This probably reflects the inability of suppliers to meet deadlines, and as a result, a lowering of the trust level. The more frequently encountered problems in construction were: 1. skip, cut or broken stitches 2. excessive loose/tight tension of seams and stitching 3. unsightly overlap stitches 4. seams twisted, puckered and pleated 5. distorted, misaligned seams 6. Button missing, misplaced, insecure 7. uncut buttonhole, noticeable bulge, poorly cut 8. needle cut or needle chew 9. buttons/buttonholes not aligned causing noticeable bulge 10. raw edges 11. uneven, misaligned placket 12. misplaced, uneven setting of labels 13. misaligned, uneven setting of the cuff. In terms of appearance, the problems most often encountered were: 1. stains and soils 2. threads not trimmed 3. generally untrimmed garment 4. wrong shade after washing 5. holes after washing 6. streak lines. There is a fabric problem which was often mentioned, namely: 1. substitution or poor math of color or print pattern when compared to master swatches. The more frequently encountered problems in packaging were: 1. missing, misplaced size ticket/hand tag. 2. incorrect type of information printed. As a result of this study, it was deduced that garment manufacturing companies still need to improve their quality control system especially in the In-process and finishing stages. A more efficient and thorough Q.C. system will be able to reduce problems in construction and appearance, thereby increasing the volume of business between garment manufacturing companies and the buyers.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Clothing trade -- Philippines -- Quality control